O leitor Gerardo Mello Mourão - Oliveira, Lucia Maria Alves Maia de (2008)
The writer’s imaginary and aesthetical inclinations are inserted in the historical and cultural context which involves them. However, besides experiencing the social tensions of his time, the writer searches for his autonomy as a literary creator, absorbing and reinterpreting the tradition. Thus, in the analysis of literary project of Gerardo Mello Mourão from (Jan., 8th, 1917 to March, 9th 2007), we outline firstly, a historical and cultural panel of the period his work was created with O Valete de Espadas (1960). Such investigation receives the theoretical critical orientation of Antronio Candido’s, Literature and Society (2000), Wilson Martins’, História da Intelectualidade Brasileira (1996), Gilberto de Mello Kujawski’s, A Crise do Século XX (1991), Vitor Manuel de Aguiar e Silva’s, Teoria da Literatura (1973) Pierre Bourdieu’s discussive pressuposition, The Rules of Art (2005) and Dominique Maingueneau with The context of the Literary work (2001). Moreover, we investigated the philosophical and aesthetical tendency of the period which interrelates with the writer’s critical positioning regarding the world around him as well as with his notion about literary writing. At the light of theoretical categories such as “Misreading” (Harold Bloom) and intertextuality (Julia Kristeva), we inquired into the 2nd chapter, the literary and critical work, Gerardo Melo Mourão’s interviews and speeches with the purpose of learning about a dialogue which is creative and traditional. In such analysis, the critical writings which were base for our reflexions were: A Angústia da Influência (1991) and Um Mapa da Desleitura (1995) by Harold Bloom as well as Palavras da Crítica (1992), organized by José Luis Jobim. In the final part of the research we observed the discursive intercourse that Gerardo Mourão keeps with other writers searching for a space of autonomous emancipation.